The Irish Helicobacter pylori Working Group consensus for the diagnosis and treatment of H. pylori infection in adult patients in Ireland. Issue 5 (May 2017) - Smith, Sinead; Boyle, Breida; Brennan, Denise; Buckley, Martin; Crotty, Paul; Doyle, Maeve; Farrell, Richard; Hussey, Mary; Kevans, David; Malfertheiner, Peter; Megraud, Francis; Nugent, Sean; et al.
Abstract : Background: Irish eradication rates for Helicobacter pylori are decreasing and there is an increase in the prevalence of antibiotic-resistant bacteria. These trends call into question current management strategies. Objective: To establish an Irish Helicobacter pylori Working Group (IHPWG) to assess, revise and tailor current available recommendations. Methods: Experts in the areas of gastroenterology and microbiology were invited to join the IHPWG. Questions of relevance to diagnosis, first-line and rescue therapy were developed using the PICO system. A literature search was performed. The 'Grading of Recommendations Assessment, Development and Evaluation' approach was then used to rate the quality of available evidence and grade the resulting recommendations. Results: Key resultant IHPWG statements (S), the strength of recommendation and quality of evidence include S8: standard triple therapy for 7 days' duration can no longer be recommended (strong and moderate). S9: 14 days of clarithromycin-based triple therapy with a high-dose proton pump inhibitor (PPI) is recommended as first-line therapy. Bismuth quadruple therapy for 14 days is an alternative if available (strong and moderate). S12: second-line therapy depends on the first-line treatment and should not be the same treatment. The options are (a) 14 days of levofloxacin-based therapy with high-dose PPI, (b) 14 days of clarithromycin-based triple therapy with high-dose PPI or (c) bismuth quadruple therapy for 14 days (strong and moderate). S13: culture and antimicrobial susceptibility testing should be performed following two treatment failures (weak and low/very low). Conclusion: These recommendations are intended to provide the most relevant current best-practice guidelines for the management of H. pylori infection in adults in Ireland.